Relationships between extreme flows and microbial contamination in inland recreational swimming areas. (7th April 2022) - Vincent, Kathryn; Starrs, Danswell; Wansink, Victoria; Waters, Natasha; Lal, Aparna
Abstract: Inland recreational swimming sites provide significant social value globally. This study focused on public recreational swimming sites across the Murrumbidgee River and its tributaries in the Australian Capital Territory (ACT) throughout the swimming season (September–April) from 2009 to 2020 to determine whether high intestinal enterococci concentrations could be predicted with flow exceedance and routinely monitored physical and chemical parameters of water quality. Enterococci concentrations were positively correlated with the turbidity associated with high-flow conditions. The predictive accuracy of high enterococci levels during high-flow conditions was good (mean percentage correctly classified, 60%). The prediction of high enterococci levels at low flows was significantly less reliable (mean percentage correctly classified, 12–15%). As the ACT is expected to experience decreases in rainfall overall but increases in extreme rainfall events due to climate change, understanding the drivers of elevated intestinal enterococci under extreme flow conditions remains important from a public health perspective. HIGHLIGHTS: Climate change is anticipated to increase the frequency and magnitude of extreme rainfall. Extreme riverine flows were associated with high enterococci concentration. High flows and turbidity were good predictors of high enterococci concentrations. High enterococci during low flows were not well explained by the water quality or flow. Graphical Abstract